1998
DOI: 10.2135/cropsci1998.0011183x003800010030x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Chemical Controls of Thatch and Their Influence on Rootzone Nutrients in a Bentgrass Green

Abstract: Thatch accumulation is a serious problem in densely grown turfgrass maintained under low mowing heights. Opinions differ concerning effectiveness of cultural and chemical controls of thatch. The objectives of these studies were to determine the effectiveness of mechanical and chemical treatments in controlling thatch and their influence on soil nutrient retention and pH in a creeping bentgrass (Agrostis palustris Huds.) green growing on a U.S. Golf Association (USGA) rootzone. Thatch control treatments were ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Golf course fairways and greens are often managed with core cultivation during the spring or fall to control thatch, alleviate surface compaction, enhance water infiltration, and stimulate root and shoot growth [9][10][11][12][13][14]. Although a limited amount of thatch is beneficial to lessen weed invasion, moderate soil temperatures, and enhance turf durability, an excessive thatch mat can reduce water infiltration and hydraulic conductivity, increase disease and pest pressure, and reduce cold temperature tolerance [11,13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Golf course fairways and greens are often managed with core cultivation during the spring or fall to control thatch, alleviate surface compaction, enhance water infiltration, and stimulate root and shoot growth [9][10][11][12][13][14]. Although a limited amount of thatch is beneficial to lessen weed invasion, moderate soil temperatures, and enhance turf durability, an excessive thatch mat can reduce water infiltration and hydraulic conductivity, increase disease and pest pressure, and reduce cold temperature tolerance [11,13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have reported thatch-mat thickness data (White and Dickens, 1984;Berndt et al, 1990;Callahan et al, 1997Callahan et al, , 1998McCarty et al, 2005McCarty et al, , 2007Barton et al, 2009;Fu et al, 2009). Measurements have been made on uncompressed thatch (Callahan et al, 1997;McCarty et al, 2007;Berndt, 2008;Fu et al, 2009) and compressed thatch (White and Dickens, 1984;Mancino et al, 1993;Callahan et al, 1997Callahan et al, , 1998.…”
Section: Thickness Of Thatchmentioning
confidence: 99%
“…Measurements have been made on uncompressed thatch (Callahan et al, 1997;McCarty et al, 2007;Berndt, 2008;Fu et al, 2009) and compressed thatch (White and Dickens, 1984;Mancino et al, 1993;Callahan et al, 1997Callahan et al, , 1998. Berndt (2008) reported that the uncompressed thickness of hybrid bermudagrass thatch-mat from Tifdwarf and TifEagle pu ing greens averaged 32 mm.…”
Section: Thickness Of Thatchmentioning
confidence: 99%
See 1 more Smart Citation
“…A cultivation method widely accepted by vegetable growers is the use of Fairways comprise approximately one-third of the managed turf of a typcial golf course (Watson et al, 1992;Lyman et al, 2007), which may be adjacent to surface waters such as streams, ponds and lakes. Golf course fairways and greens are often managed with core cultivation during the spring or fall to control thatch, stimulate root and shoot growth, alleviate surface compaction, and enhance water infiltration (Beard, 1973;White & Dickens, 1984;Turgeon, 1985;Carrow et al, 1987;Dunn et al, 1995, Callahan et al, 1998. Solid tine core cultivation requires a reduced amount of labor and is less disruptive to the surface of the turf but is believed to cause localized compaction.…”
Section: Introductionmentioning
confidence: 99%